1968
DOI: 10.1128/jb.96.4.1214-1224.1968
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Deoxyribonucleic Acid Replication and Cell Division in Escherichia coli B/r

Abstract: Synchronous cultures of Escherichia coli strain B/r were used to investigate the relationship between deoxyribonucleic acid (DNA) replication and cell division. We have determined that terminal steps in division can proceed in the absence of DNA synthesis. Inhibition of DNA replication with nalidixic acid prior to the start of a new round of replication does not stop cell division, which indicates that the start of the round is not essential in triggering cell division. Inhibition of DNA replication at any tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

1971
1971
1988
1988

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 19 publications
6
56
0
Order By: Relevance
“…auxotroph by using amino acid starvation [12]. The doubling time of the chromosomal DNA was about 120 min [7]; this approximately corresponding with our experimental data. It was shown that in E. coli K12, the initiation point of the chromosome replication was found to be located between the lysine and histidine markers, and the order of replication was clockwise [1,4].…”
Section: Discussionsupporting
confidence: 87%
“…auxotroph by using amino acid starvation [12]. The doubling time of the chromosomal DNA was about 120 min [7]; this approximately corresponding with our experimental data. It was shown that in E. coli K12, the initiation point of the chromosome replication was found to be located between the lysine and histidine markers, and the order of replication was clockwise [1,4].…”
Section: Discussionsupporting
confidence: 87%
“…In this study, we have assumed, as have others (see [4]), that minicells are typical cell poles. This assumption is based on the observation that minicells are always produced at the cell poles and that the process of septation at the poles is apparently normal as judged by electron microscopy [4] and is under the same controls as division at the center of the cell [23,24,4]. In addition, murein synthesis at these polar sites appears to be normal since the murein composition (both the glycan chain length [25] and the degree of peptide cross-bridging [ll]) is typical.…”
Section: Discussionmentioning
confidence: 99%
“…These constructions grow on a rich medium with added glutathione or cysteine. In addition, the cells showed the long filamentous morphology which is characteristic of impaired DNA synthesis [116]. These results suggest that glutaredoxin is essential for ribonucleotide reduction and the preferred cofactor for ribonucleotide reductase in vivo.…”
Section: Glutaredoxin Systemmentioning
confidence: 82%